HOW ENGLISH TEACHERS’ LESSON PLANS INCORPORATE LEARNING AND INNOVATION SKILLS - Tamela, Ellis; Tara Mustikaning Palupi; Hanip Pujiati (Universitas Islam Lamongan, 2024)
English instruction in Indonesia now includes learning and innovation skills, also known as the 4Cs: communication, cooperation, critical thinking, and creativity. The purpose of this study is to determine how much eighth-grade English teachers use 4Cs skills in their lesson plans. This content analysis uses information from 10 eighth-grade lesson plans from various schools in Jakarta and Bekasi. The learning objectives, learning materials, methods, and assessment were the main topics of the lesson plan components. Even though there were dominating indicators from each skill—communication skill indicators were the most common and creative indicators were the least—nine lesson plans were identified to incorporate 4C. Furthermore, learning objectives were only found in the communication, collaboration, and critical thinking skills; learning media was found in the communication skills; and assessment was found in the communication, collaboration, and critical thinking skills. The lesson plan components that integrated all skills were learning activities and other lesson plan components.